2005
DOI: 10.1037/0735-7028.36.6.642
|View full text |Cite
|
Sign up to set email alerts
|

Improving mental health services for Latino and Asian immigrant elders.

Abstract: Given the changing demographics of the aging population in the United States, it is likely that professional psychologists will encounter elderly clients from diverse backgrounds in their practice. Asians and Latinos represent the 2 fastest growing groups of elderly immigrants. This article offers information and practical suggestions to assist clinicians working with elderly Asian and Latino immigrant clients. Specific recommendations for enhancing assessment and treatment efficacy with these populations are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 33 publications
0
20
1
Order By: Relevance
“…In addition, older East Asian immigrants tend to maintain their own cultural values and beliefs, which create conflicts with their adult children who are highly acculturated, and misunderstandings with others who are culturally or ethnically diverse (Weisman et al, 2005). For example, Mui and Kang (2006) found that the cultural gap between older Asian immigrants and their adult children caused depressive symptoms, which negatively affected their health.…”
Section: Related Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, older East Asian immigrants tend to maintain their own cultural values and beliefs, which create conflicts with their adult children who are highly acculturated, and misunderstandings with others who are culturally or ethnically diverse (Weisman et al, 2005). For example, Mui and Kang (2006) found that the cultural gap between older Asian immigrants and their adult children caused depressive symptoms, which negatively affected their health.…”
Section: Related Literature Reviewmentioning
confidence: 99%
“…Substantial evidence suggests that older East Asian immigrants experience more adaptation difficulties and perceive more acculturative stress than younger immigrants (Berry, 1992; Diwan, Jonnalagadda, & Balaswamy, 2004; Oh & Sales, 2002). The primary reason for this evidence is that older East Asian immigrants have a limited proficiency of English and communication problems with others (Lai, 2004; Nicassio, 1983; Weisman et al, 2005). These studies show that limited English skills resulted in social isolation and negative psychological symptoms, such as depression and anxiety, among older East Asian immigrants.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Familismo values emphasize that nuclear and extended families should be included in all aspects of caregiving, from daily self-care assistance to decision-making involvement (Galanti 2003). Emphasis on familial caregiving may lead Hispanics to refrain from seeking support from external sources (Weisman et al 2005). Machismo, the conception of masculinity in Hispanic culture, may include qualities such as emotional distancing and authoritarianism (Torres, Solberg, and Carlstrom 2002), which are associated with conflict in marital relationships and may translate into negative support (Tamez 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Currently it is estimated that 11% (i.e., approximately 35 million) of the Muslim population in the United States are older adults (Hetzel & Smith, 2001;Weisman, Feldman, Gruman, Rosenberg et al, 2005). Older adults in general are increasing at a rapid pace in the United States, given the estimate that 20% of the US population is projected to be 65 years old by 2030, and this increases their vulnerability to mental illness due to isolation, loneliness, and declining physical and mental abilities (Center for Disease Control and Prevention, 2002).…”
Section: Muslim Immigrants and Refugeesmentioning
confidence: 99%